Ewolucja przepisów dotyczących pogrzebu kościelnego od Kodeksu Prawa Kanonicznego z 1917 r. - Janczewski, Zbigniew (Prawo Kanoniczne, 2000)
Church funerals are to be celebrated according to the norms of the liturgical books. In these rites the Church prays for the spiritual support of the dead, it honors their bodies, and at the same time it brings to the living the com fort of hope. Many funeral regulations are also in the Canon Law. This article shows the canon norms from the year 1917 to the Code of Canon Law of the pope John Paul II.